(untitled) (Research, Society and Development, 2021)
Anarcadiaceae is one of the families of angiosperms that presents an expressive diversity in Brazil, besides its economic and medicinal importance. The objective was to perform a technological and scientific prospection about Anacardiaceae, analyzing the number of patent deposits per country, year and their international classifications (CIP), as well as to describe the profile of the scientific production in the areas of application. A scientific and technological prospection was carried out in national and international databases of articles and patents on Anacardiaceae. Patent applications started in 2012 with an increase in publications in 2015 and 2020 according to Web of Science and Scopus, respectively. Japan, the United States, and China lead with technological production included mostly in subclass A61K, and the technologies are directed mainly to medical, dental, or hygienic purposes. As for scientific production, Brazil stands out in first place in number of published articles. We conclude that the family is the source of several medical researches, and Brazil has a great biotechnological potential with its use.